Reduced intelligibility explains delayed responses to questions in older adults with hearing loss. - Whitley, Alexina; Corps, Ruth E.; Hadley, Lauren V. (Language, Cognition & Neuroscience, 2026)
Typical conversation is characterized by tightly coordinated turn-taking, meaning that listeners must begin planning their response before their partner has finished talking. But concurrently planning and comprehending incoming speech is resource intensive. This study investigates the effects of intelligibility (by manipulating stimulus presentation level) and hearing loss (through comparison of older adults with normal vs impaired hearing) on the timing of response planning using a verbal question answering task. When information critical for response planning occurred early in the question, participants were faster to answer than when it occurred late, indicating an early planning approach. Although hearing impaired participants showed slower responses than normal hearing participants when listening to conversation-level speech, they showed no change in planning strategy. Furthermore, when intelligibility was equated, groups performed similarly, suggesting that the turn-taking delays that have been reported for hearing impaired interlocutors may be driven by reduced intelligibility impacting planning.